2019
DOI: 10.1177/0047287519874131
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Analysis of Residents’ Support for Tourism Development in the UAE: A Bayesian Structural Equation Modeling Multigroup Approach

Abstract: This study examines how the demographic profiles of residents (gender, level of education, nationality, length of residency, and age) moderate the relationship between residents’ perceptions of the impact of tourism and their support for tourism development. The aim of the study was to gain knowledge on the understudied emerging countries, the underexplored geographical area of Middle East and North Africa, and most specifically on the UAE which is the most competitive destination among them. This study is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 96 publications
(168 reference statements)
4
47
1
Order By: Relevance
“…One possible reason is that expats are attracted to live in the UAE mainly in search of better economic opportunities; therefore, they would be more concerned about the economic impact while the nationals are more anxious about their country's social, cultural and environmental impacts. Nevertheless, the results of this study contradict Papastathopoulos et al, (2020); Hammad et al, (2017) and Hammad et al (2019) studies in the way it found that both local and expats perceive the positive socio-cultural aspects of tourism development while both do not perceive any negative socio-cultural aspects of tourism. Remarkably, both residents' groups (citizens and expats) showed positive overall evaluation of tourism impacts and both supported future tourism development by UAE government.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…One possible reason is that expats are attracted to live in the UAE mainly in search of better economic opportunities; therefore, they would be more concerned about the economic impact while the nationals are more anxious about their country's social, cultural and environmental impacts. Nevertheless, the results of this study contradict Papastathopoulos et al, (2020); Hammad et al, (2017) and Hammad et al (2019) studies in the way it found that both local and expats perceive the positive socio-cultural aspects of tourism development while both do not perceive any negative socio-cultural aspects of tourism. Remarkably, both residents' groups (citizens and expats) showed positive overall evaluation of tourism impacts and both supported future tourism development by UAE government.…”
Section: Discussioncontrasting
confidence: 99%
“…Expats expressed greater positive perceptions of the economic impacts of tourism. This finding goes on line with the Papastathopoulos et al, (2020); Hammad et al, (2017) and Hammad et al (2019) studies who also found that expats have more positive perceptions of the economic impacts of tourism, while national residents have more concerns regarding the social, cultural, and environmental impacts of tourism. One possible reason is that expats are attracted to live in the UAE mainly in search of better economic opportunities; therefore, they would be more concerned about the economic impact while the nationals are more anxious about their country's social, cultural and environmental impacts.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Education may improve the communication skills of community members, as well as their awareness levels concerning tourism-related issues (Sinclair-Maragh, 2017). Papastathopoulos et al (2019) indicated on differences in perceptions of tourism development impacts depending on education level. They found that a higher education level of residents has a more powerful influence on the residents' perception of cultural, social, and environmental impacts.…”
Section: Impacts Of Education Level On Local Populations' Attitudes Tmentioning
confidence: 99%